Enhanced QSVM with elitist non‐dominated sorting genetic optimisation algorithm for breast cancer diagnosis - P, Jose; Hariharan, Shanmugasundaram; Madhivanan, Vimaladevi; N, Sujaudeen; Krisnamoorthy, Murugaperumal; Cherukuri, Aswani Kumar (IET quantum communication, 2024)
Machine learning has emerged as a promising method for predicting breast cancer using quantum computation techniques. Quantum machine learning algorithms, such as quantum support vector machines (QSVMs), are demonstrating superior efficiency and economy in tackling complex problems compared to traditional machine learning methods. When compared with classical support vector machine, the quantum machine produces remarkably accurate results. The suggested quantum SVM model in this study effectively resolved the binary classification problem for diagnosing malignant breast cancer. This work introduces an enhanced approach to breast cancer diagnosis by integrating QSVM with elitist non‐dominated sorting genetic optimization (ENSGA), leveraging the strengths of both techniques to achieve more accurate and efficient classification results. ENSGA plays a crucial role in optimising QSVM parameters, ensuring that the model attains the best possible classification accuracy while considering multiple objectives simultaneously. Moreover, the quantum kernel estimation method demonstrated exceptional performance by achieving high accuracy within an impressive execution time of 0.14 in the IBM QSVM simulator. The seamless integration of quantum computation techniques with optimisation strategies such as ENSGA highlights the potential of quantum machine learning in revolutionising the field of healthcare, particularly in the domain of breast cancer diagnosis. The work presented here focuses on quantum machine learning and related studies. This article focuses on elitist non‐dominated sorting genetic optimization algorithm for efficient breast cancer diagnosis.